MAIN DIFFICULTIES IN DEVELOPING WRITING SKILLS OF LEARNERS - Z. Tukhtasinova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the challenges faced by students in developing their writing skills, particularly in English as a second language (ESL) settings. It explores various factors that hinder students’ progress in writing, including lack of motivation, inadequate vocabulary and language proficiency, poor writing strategies and planning, unfamiliarity with genre conventions, limited feedback and assessment practices, and technological barriers. The article emphasizes the importance of addressing these challenges and provides suggestions for educators and institutions to enhance the teaching and learning of writing skills.